Victimization risks and routine activities: A theoretical examination using a gender-specific and domain-specific model - Mustaine, Elizabeth Ehrhardt (American journal of criminal justice, 1997)
This paper examines female and male victimization risks in general and in three domains: home, work, and leisure/public. In doing so, the analysis is based on a popular victimization model: the routine activities/lifestyle theory of victimization. There are several critiques of the routine activities/lifestyle theory research at present. Most tests of this theory use a sample of victims that does not distinguish between specific populations. Further, research on victimization risks needs domainspecific models of victimization because lifestyle can encompass a large variety of behaviors in several different settings, all of which do not have the same risk of victimization (Lynch, 1987). Analyses using data from the National Crime Survey’s Victim Risk Supplement (1983) indicate the importance of analyzing specific populations and domains in any evaluation of routine activities/lifestyle victimization theory because the determinants of victimization are not identical between men and women or between the domains of home, work, and leisure/public.